Strategies of Green Transformation in Production Operation of Power Battery Enterprises Under the Dual- Carbon Target - Zhang Shuai; Purwanto Purwanto (AIBPM Publisher, 2026)
Following the Paris Climate Agreement, global efforts to reduce carbon emissions have shifted from policy commitments to practical implementation. Electricity generation and transportation remain two of the largest sources of carbon emissions. Although new energy vehicles (NEVs) contribute to the decarbonization of the transportation sector, the production of power batteries continues to generate substantial emissions. This study examines the green transformation strategy of CATL under China's